QRIS MEDIATION MODEL: BRIDGING YOUTH ENTREPRENEURIAL ORIENTATION AND DIGITAL LITERACY TO MSME SUSTAINABILITY - Aghniya, Arina; Jaya, Nurul Aini Dwi; Pratama, Aryan Agus; Zainal, Nur Hikmah (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This study empirically examines how youth-driven Entrepreneurial Orientation (EO) and Digital Literacy (DL) enhance MSME sustainability through the mediating role of Quick Response Code Indonesian Standard (QRIS) utilization. Addressing the limited structural evidence on digital payment adoption as a mechanism that transforms internal human capital into measurable sustainable outcomes, this research contributes novel insights into the digitalization–sustainability nexus. A quantitative explanatory design was employed using survey data collected from youth MSME owners in Makassar. The structural relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings demonstrate strong explanatory power (R² MSME Sustainability = 0.781; QRIS Utilization = 0.580) and confirm consistent partial mediation. QRIS utilization emerged as the strongest direct predictor of MSME sustainability and significantly amplified the total effects of both EO and DL. These results highlight the strategic importance of integrating human capital development with standardized digital payment systems to accelerate resilient and inclusive economic growth among young entrepreneurs. This study is among the first to structurally validate the sequential pathway linking EO and DL to MSME sustainability through QRIS adoption.